Statistical Analysis of Compact Single-source Flares Observed by STIX - Michalina Litwicka; Tomasz Mrozek; Arun K. Awasthi; Marek Siarkowski; Marek Stęślicki; Janusz Sylwester; Barbara Sylwester (The Astrophysical Journal)
X-ray emissions from solar flares provide a comprehensive overview of the spatial and spectral behaviors of high-temperature plasma in the solar atmosphere. In particular, compact flares are one of the best candidates for quantifying the geometrical properties of the X-ray source, which is crucial in the estimation of flare energetics. Accordingly, we present a statistical investigation of 550 flares showing one compact source in images reconstructed with the MARLIN, Expectation Maximization, and Forward Fit algorithms in the 6–10 keV soft X-ray (SXR) energy channel of the Spectrometer Telescope for Imaging X-rays (STIX), on board Solar Orbiter. We compare various properties of the sources, reconstructed with the aforesaid algorithms, which show consistency. We further test different approaches to estimating source sizes. We find better agreement between the tested algorithms using the 50% signal contour for size estimation instead of the commonly used 50% isophote. Thermal–nonthermal flare plasma parameters and energetics are investigated for a subset of flares exhibiting significant enhancement in the 12–20 keV hard X-ray (HXR) energy channel. While strong correlations are found between the emitted SXR and HXR flux with temperature, the HXR flux with nonthermal energy, and thermal with nonthermal energy, plasma parameters were not significantly correlated with the flare size or volume. The thermal–nonthermal emission partition during compact flares, characterized using the Neupert effect, is revealed only for 40% of events. We find the fraction of HXR fluence to SXR flux to be positively correlated with volume while moderately anticorrelated with density. This indicates that tenuous flare loops emit relatively less SXR emission as a response to deposited energy, compared to dense loops.